Degradation behaviour of PCL/PEO/PCL and PCL/PEO block copolymers under controlled hydrolytic, enzymatic and composting conditions. (February 2017) - Ponjavic, Marijana; Nikolic, Marija S.; Nikodinovic-Runic, Jasmina; Jeremic, Sanja; Stevanovic, Sanja; Djonlagic, Jasna
Abstract: Short-term hydrolytic and enzymatic degradation of poly( ε -caprolactone) (PCL), one series of triblock (PCL/PEO/PCL) and the other of diblock (PCL/PEO) copolymers, with a low content of hydrophilic PEO segments is presented. The effect of the introduction of PEO as the central or lateral segment in the PCL chain on copolymer hydrolysis and biodegradation properties was investigated. FTIR results revealed higher hydrolytic degradation susceptibility of diblock copolymers due to a higher hydrophilicity compared to PCL and triblock copolymers. Enzymatic degradation was tested using cell-free extracts of Pseudomonas aeruginosa PAO1, for two weeks by following the weight loss, changes in surface roughness, and changes in carbonyl and crystallinity index. The results confirmed that all samples underwent enzymatic degradation through surface erosion which was accompanied with a decrease in molecular weights. Diblock copolymers showed significantly higher weight loss and decrease in molecular weight in comparison to PCL itself and triblock copolymers. AFM analysis confirmed significant surface erosion and increase in RMS values. In addition, biodegradation of polymer films was tested in compost model system at 37 °C, where an effective degradation of block copolymers was observed.